QUESTIONS OF THE STUDY OF THE HISTORICAL ROOTS OF COMPARATIVE RUSSIAN LITERATURE - Murodova Khurshida Bakhtiyorovna, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
This article deals with issues related to comparative literature.